Peningkatan Ketepatan Shooting Pada Permainan Futsal Melalui Permainan Sasaran Target Siswa Usia 14-15 Tahun - Ahmad Firmansah; Dodi Nurhidayat; Lukmanul Hakim (Departement of Mathematics Education, 2024)
This research aims to determine the effect of target game practice on shooting accuracy in extracurricular futsal games at SMP Negeri 1 Mandalawangi. This type of research is experimental research using a One-Group Pretest-Posttest Design research design. The population in this study were all futsal players at SMP Negeri 1 Mandalawangi, totaling 14 players. The sampling technique used total sampling with a total sample of 14 people. This research was treated with a target game practice method. The treatment given by researchers was 16 meetings with a frequency of 2 times a week for 8 weeks or 2 months. The instrument in this research was a test of shooting accuracy at the target. Data analysis used the t test (paired sample t test) at a significance level of 0.05, with the prerequisite normality test (Shapiro Wilk) and homogeneity test (Levene's test). From the results obtained, it is known that there is a significant influence of training using target games on shooting accuracy in extracurricular football games at SMP Negeri 1 Mandalawangi. The results can be seen that tcount is 2.598 and t table (df 13) 2.160 with a significance p value of 0.022. Because tcount is 2.598 > ttable ) 2.160, and the significance value is 0.022 <0.05, then these results show that there is a significant effect of training using target aiming games on shooting accuracy.